Islamic capital market In Maldives: a reform-oriented analysis - Shujau, Mohamed; Hassan, Rusni; Mohd Yusoff, Syarah Syahira; Muneeza, Aishath (IIUM Press, 2022)
This study analyses legal and regulatory framework of Islamic capital market (ICM) in the Maldives to find out the legal reform required to further develop ICM in the country. The regulatory authority for ICM in the Maldives is the Capital Market Development Authority which has set up an apex Shari’ah Advisory Council to seek advice on Shari’ah related matters and has enacted the regulations required for ICM. This study adopts doctrinal legal research and qualitative study using the content analysis approach. It is imperative to note that only limited research has been found on the subject and as such, it is anticipated that findings of this research will assist the policymakers to understand the legal reform required to further strengthen ICM in the Maldives. Findings of this study reveal that there is a need to amend the Securities Act (2006) to recognize Shari’ah Advisory Council for capital markets as a statutory body. The findings suggest the Shari’ah Advisory Council to make their decision binding, and the regulations enacted for ICM need to be amended considering the existing hiccups and challenges faced.